(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Introduction. The strategic task of the state is to ensure the proper health of children, the implementation of preventive measures aimed at preventing diseases that can be caused by malnutrition, creating conditions for improving the demographic situation in Ukraine. Children do not have a well-formed model of consumer behavior, so when choosing products and services, schoolchildren become vulnerable to aggressive marketing policies of business. Therefore, state regulation of food safety for children should not be considered as the only possible option, but as one element of a comprehensive marketing mechanism for managing schoolchildren food safety with the involvement of stakeholders. The purpose of the article is to determine the conceptual basis of interaction between the subjects of the marketing mechanism of schoolchildren food safety management. Results. School-age children are becoming market participants. The realization of the rights acquired by the child is based on the physical and mental immaturity of the child, which necessitates the specific protection and care. The marketing mechanism involves involving the state and the marketing subjects in solving the urgent problems of managing the child nutrition. The structure of the marketing mechanism contains the following components: "login" in the system; "exit" of the system; the internal structure of a marketing mechanism containing several elements. The article describes the characteristics of the elements of the marketing mechanism for managing child nutrition and the content of management functions. It is advisable to consider the three levels of child nutrition management, each with different subjects of the marketing mechanism (personal, social and system levels). The implementation of integrated child safety management at all three levels simultaneously provides the opportunity to gain synergies and achieve the most significant results from the coherence of interaction between all actors. The core of the child safety management marketing mechanism is the interaction of its key actors (namely, the management entity and the marketing entities). The article provides a graphical interpretation of the interaction model of subjects of the marketing mechanism of food safety management of school-age children. The metric interaction of the subjects of the marketing mechanism — the index of group reciprocity of the marketing subjects — characterizes the interrelation of the subjects, the cohesion and the closeness of their interaction. The conceptual principles of the interaction of subjects of the marketing mechanism determine its characteristic features. Conclusions. According to the results of the research, the key idea of ​​the interaction of the subjects of marketing mechanism is identified as the core model of the marketing mechanism for managing the safety of food of school-age children. It is proved that food safety management has to take place at three levels, each of which corresponds to different subjects of the marketing mechanism: personal, social and system levels. The implementation of integrated child safety management at all three levels simultaneously provides the opportunity to gain synergies and achieve the most significant results from the coherence of interaction between all subjects. Determining the conceptual bases of the model and approaches to determining the parameters of functioning of the marketing mechanism of food safety management of school-age children requires further research.